PENINGKATAN KAPASITAS PRODUKSI MELALUI PENGHITUNGAN WAKTU BAKU, TATA LETAK FASILITAS, SERTA PEMBERIAN KOMPENSASI DI PT SURYA PUTRA BARUTAMA - Wijaya, Chandra; Sutapa, Nyoman (Jurnal Titra, 2014)
PT Surya Putra Barutama was not able to meet the market demand i.e. 500 units/month, since their production capacity was only 300 units/month. Therefore, to solve that problem we need to improve that capacity by calculating the standard time, production facility layouting, and calculating a new reward standard. At the end of this project, we found that, now the production capacity is 600 units/month.